KETERAMPILAN DASAR MENGAJAR - Dewi Dyah Widyastuti (JURNAL MITRA MANAJEMEN, 2013)
ABSTRACTProfessionallecturers must have four competencies: pedagogical, cognitive,personality, and social. To support the work of professionalism required of the mostbasic skills. If the skill is done repeatedly, it will become a regular thing done everyimplement teaching.